THE IMPLEMENTATION OF CREATING SHARED VALUE (CSV) AND ITS IMPACT ON COMPANY’S PERFORMANCE - Tyas, Fatma Hartining; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The objective of this research is to analyze the implementation of CSR toward company’s performance. The CSR is represented by CSV (Creating Shared Value) and the company’s performance is represented by financial performance, human resource, and corporate image. This study employs interview as the source of primary data and company’s report and publications as the secondary data. The findings of the study reveals that CSR activities have impact toward the company’s performance as shown by the three indicators, consisting of financial performance, corporate image, and human resource. From this study, it can also be concluded that the CSV activities undertaken by PT PKG a positive impact and significant enough to company performance. This is evidenced by the increasing ratio of a company's financial year, but it also PT PKG experienced an increase in sales of their products, it is because the PT PKG has a good image in the public perspective. And human resources owned by PT PKG have increased as more and more human resources really have the expertise as required by the company in carrying out its activities.Keyword: CSR, CSV, and company’s performance